2021
DOI: 10.3390/jcm10194502
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Expansion after Non-Skin-Sparing Mastectomy: A Comparative Study of Expansion Courses of Prepectoral and Subpectoral Tissue Expander Placement with Acellular Dermal Matrix

Abstract: Although skin- or nipple-sparing mastectomy has been popular in the treatment of breast cancer, the radical excision of breast tissue is unavoidable in certain circumstances. However, the ability of an acellular dermal matrix (ADM) to expand remains questionable, and this situation may further hinder tissue expansion. From October 2017 to January 2020, patients who underwent immediate breast reconstruction with tissue expander placement using ADM whose initial fill volume was less than 50 mL were retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It is then possible to adapt the reconstruction in the second surgical time according to the new anatomical framework and the patient’s expectations. The subsequent expansion thus also allows for the use of larger implants that would have been contraindicated in a DTI reconstruction with prosthesis and ADM [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is then possible to adapt the reconstruction in the second surgical time according to the new anatomical framework and the patient’s expectations. The subsequent expansion thus also allows for the use of larger implants that would have been contraindicated in a DTI reconstruction with prosthesis and ADM [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Sbitany and colleagues, the surgical time was prolonged with subpectoral expander placement compared to prepectoral device placement [4.3 (range, 3.5–4.8) versus 3.9 (3.3–4.3) hours, P=0.001] ( 30 ). Likewise, in Asian patients a prolonged surgical time with subpectoral expander placement compared to prepectoral has been reported (76.56 versus 58.46 minutes, P<0.001) ( 23 ). Remarkably, evaluating the prepectoral versus subpectoral technique with propensity score matching, authors from the University of Texas Southwestern Medical Center determined there was no associated change in surgical time implementing either one approach or the other (103 versus 104 minutes, P=0.891) ( 29 ).…”
Section: Complicationsmentioning
confidence: 96%
“…Despite some studies have reported comparable rates of complications between prepectoral and subpectoral TE placement ( 19 - 23 ), other reports have highlighted that rates of complications differ depending on the plane of prosthesis placement for two-stage IBBR. Initial reports from Nahabedian and Cocilovo indicated that the percentage of patients who had surgical complications was 20.5% and 22% for the prepectoral and partial subpectoral cohorts, respectively ( 17 ).…”
Section: Complicationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have analyzed ADM use in immediate prosthetic reconstruction without controlling for plane of implant placement or solely analyzed outcomes by plane of implant placement without controlling for use of ADM ( 5 , 19 - 25 ). The existing reports analyzing ADM use in pre-pectoral breast reconstruction after NSM, are low powered, allowing for less accurate outcome profiles ( 26 - 30 ).…”
Section: Introductionmentioning
confidence: 99%